(untitled) (Journal of Digital System Development, 2024)
The growing reliance on technological devices among children, mainly through mobile games, poses risks such as addiction while also offering opportunities for educational enhancement. In Malaysia, only 36% of primary school students achieve excellence in mathematics, a situation worsened by negative attitudes and anxiety towards the subject. Traditional teaching methods have proven inadequate in addressing these challenges. To tackle this issue, MyMathly, a gamified persuasive mobile game prototype, is developed to motivate students and improve their proficiency in mathematics. A pilot study has been conducted to evaluate the persuasiveness and effectiveness of the MyMathly prototype using the Computer System Usability Questionnaire (CSUQ) as an instrument. It has been evaluated across four key elements: ease of use, ease of learning, information structure, and user satisfaction. The findings indicate that MyMathly successfully engages students, improves their motivation, and positively influences their behaviour towards learning mathematics. This study contributes valuable insights into designing and implementing gamified educational tools that align with the Malaysian curriculum, addressing cultural relevance and educational needs.